The addition of discrimination inhibitors stimulations discrimination potential and N2O emissions were linked to predation among microorganisms in long term nitrogen application and straw returning systems - Jia, Chunhua; Zhou, Guixiang; Ma, Ling; Qiu, Xiuwen; Zhang, Jiabao; Wang, Jingkuan; Zhang, Congzhi; Chen, Lin; Ma, Donghao; Zhao, Zhanhui; Xue, Zaiqi (Frontiers in Microbiology, 2024)
Introduction: Ammonia oxidizing archaea (AOA) and ammonia oxidizing bacteria (AOB) have been proven to be key microorganisms driving the ammonia oxidation process. However, under different fertilization practices, there is a lack of research on the impact of interaction between predators and AOA or AOB on nitrogen cycling at the multi-trophic level. Methods: In this study, a network-oriented microscopic culture experiment was established based on four different long-term fertilization practices soils. We used the nitrification inhibitors 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxide-3-oxyl (PTIO) and 3, 4-Dimethylpyrazole phosphate (DMPP) inhibited AOA and AOB respectively, to explore the impact of interaction between protists and AOA or AOB on nitrogen transformation. Results: The results showed that long-term nitrogen application promoted the potential nitrification rate (PNR) and nitrous oxide (N2O) emission, and significantly increased the gene abundance of AOB, but had no obvious effect on AOA gene abundance. DMPP significantly reduced N2O emission and PNR, while PTIO had no obvious effect on them. Accordingly, in the multi-trophic microbial network, Cercozoa and Proteobacteria were identified as keystone taxa of protists and AOB respectively, and were significantly positively correlated with N2O, PNR and nitrate nitrogen. However, Nitrososphaerota archaeon as the keystone species of AOA, had an obvious negative linkage to these indicators. The structural equation model (SEM) showed that AOA and AOB may be competitors to each other. Protists may promote AOB diversity through direct trophic interaction with AOA. Conclusion: The interaction pattern between protists and ammonia-oxidizing microorganisms significantly affects potential nitrification rate and N2O emission, which has important implications for soil nitrogen cycle.